India’s Soft Power as a Pillar of Foreign Policy - Aadil Ahmad Shairgojri (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2021)
The power dynamics of nation-states around the world have undergone a significant change in the twenty-first century with regard to how governments define and demonstrate their authority. Since today's political world is becoming increasingly interconnected, governments have no choice but to spend heavily in both their soft and hard power matrices. Because of the current state of world politics, India has a better chance than ever before of becoming a major player in international affairs. In India and around the world, the election of Prime Minister Narendra Modi has caused a sea change in public opinion about the dangers of religious militarism. These rights have become increasingly popular due to the increase of Hindutva rights. "Soft power" refers to the ability of a nation to achieve its foreign policy goals and objectives without resorting to coercion. With or without the use of "hard power," which can refer to methods such as the use of force or other very effective diplomatic initiatives, it is still a critical tenet of foreign policy. Hard power can be utilized in international and bilateral diplomacy to create a more expansive narrative. Economic, sociocultural, and even civilizational aspects all play a significant part in this wide-ranging topic. It all starts with messaging, which can be done through official channels like speeches and press conferences, or through the wide variety of media outlets available in today's hyper-connected world. Using India's "soft power" in international politics is the primary subject of this article.